Eksistensi Penerapan Sanksi Alas Bide dalam Penyelesaian Perkara Kekerasan Dalam Rumah Tangga (KDRT) di Kabupaten Bengkayang, Kalimantan Barat - Chusnul Qotimah Nita Permata; Rastini (CV Rewang Rencang, 2022)
Customary law is one of the laws that adjudicate a case that occurs in an area. The existence of customary law has been recognized in laws and regulations which are still valid and in tandem with state law. The purpose of this study was to determine the application of the Alas Bide which was applied to the customary law of Bengkayang district, West Kalimantan province in the settlement of a case in the case of Domestic Violence (KDRT). Research methods use a type of normative legal research with a type of statutory approach or Statute approach, which refers to several laws and regulations. Based on the results of the research and discussion, it can be concluded, First, the settlement of cases of domestic violence with Alas Bide in Bengkayang, West Kalimantan. Second, the existence of the use of customary law with national law.